2020
DOI: 10.18510/hssr.2020.83131
|View full text |Cite
|
Sign up to set email alerts
|

Drug-Abuse Inmates Maqasid Shariah Quality of Life: A Conceptual Paper

Abstract: Purpose of the study: The primary aim of this study is to explore the feasibility of Maqasid Shariah Quality of Life (MSQoL) in the drug-abuse inmates’ research. MSQoL is a recent theory formulated in terms of quality of life. Therefore, MSQoL proceeds to examine the association of family social support and prison climate rehabilitation on quality of life among drug-abuse inmates. Methodology: This study conceptually focused on a comprehensive analysis of MSQoL, family social support, and prison climate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…As shown by Li et al [ 32 ] and El Kazdouh et al [ 46 ], peers exert a certain influence on other teenagers by making them subconsciously want to fit into the group. Peer selection and peer socialization processes might explain why peer pressure serves as a risk factor for drug-abuse among adolescents [ 67 ]. Another study reported that strong religious beliefs integrated into society play a crucial role in preventing adolescents from engaging in drug abuse [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…As shown by Li et al [ 32 ] and El Kazdouh et al [ 46 ], peers exert a certain influence on other teenagers by making them subconsciously want to fit into the group. Peer selection and peer socialization processes might explain why peer pressure serves as a risk factor for drug-abuse among adolescents [ 67 ]. Another study reported that strong religious beliefs integrated into society play a crucial role in preventing adolescents from engaging in drug abuse [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Adolescents, for example, may demonstrate aggressive or rule-breaking behaviours that gravitate them towards peers who share similar tendencies. Such peer networks may expose them to drug use that could rapidly undermine their decision-making and actions [8,40]. Adolescents who display externalising behaviours may be more susceptible to peer pressure, feeling compelled to conform to the expectations and behaviours of their friends that revolve around drug use.…”
Section: Discussionmentioning
confidence: 99%
“…Substantially, there are at least three groups of topics (Figure 3), where the first included relationship between regression analysis, investments, risk-sharing, risk management and commerce (Ahmed & Farooq, 2018;Amaroh & Masturin, 2018;Jobst, 2009;Kammer et al, 2015;Kusuma, 2019). The second group represented a simultaneous relationship among the stock market, financial institutions, Islamism, shariah, banking, Malaysians, industry and Malaysia (Ahmed & Farooq, 2018;Hassan et al, 2018;Norbayusri Baharudin et al, 2020;Paranque & Erragragui, 2016;Shamsudheen & Rosly, 2020;Umar et al, 2018). Meanwhile, the third group represented the interrelationships among information management, business activities, economic and social effect, insurance, as well as sustainable development (Ahmed & Farooq, 2018;Heradhyaksa & Markom, 2018;Kasim et al, 2016;Nugraha et al, 2020;Yahya & Mahzan, 2011).…”
Section: Descriptive Analysis On Shariah Compliance Literaturementioning
confidence: 99%